Hyperglycemia and Risk of All-cause Mortality Among People Living With HIV With and Without Tuberculosis Disease in Myanmar (2011–2017). (28th December 2018) - Kyaw, Nang Thu Thu; Satyanarayana, Srinath; Oo, Htun Nyunt; Kumar, Ajay M V; Harries, Anthony D; Aung, Si Thu; Kyaw, Khine Wut Yee; Phyo, Khaing Hnin; Aung, Thet Ko; Magee, Matthew J
Abstract: Background: There is limited empirical evidence on the relationship between hyperglycemia, tuberculosis (TB) comorbidity, and mortality in the context of HIV. We assessed whether hyperglycemia at enrollment in HIV care was associated with increased risk of all-cause mortality and whether this relationship was different among patients with and without TB disease. Methods: We conducted a retrospective analysis of adult (≥15 years) HIV-positive patients enrolled into HIV care between 2011 and 2016 who had random blood glucose (RBG) measurements at enrollment. We used hazards regression to estimate associations between RBG and rate of all-cause mortality. Results: Of 25 851 patients, 43% were female, and the median age was 36 years. At registration, the median CD4 count (interquartile range [IQR]) was 162 (68–310) cell/mm 3, the median RBG level (IQR) was 88 (75–106) mg/dL, and 6.2% (95% confidence interval [CI], 6.0%–6.5%) had hyperglycemia (RBG ≥140 mg/dL). Overall 29% of patients had TB disease, and 15% died during the study period. The adjusted hazard of death among patients with hyperglycemia was significantly higher (adjusted hazard ratio [aHR], 1.2; 95% CI, 1.1–1.4) than among those with normoglycemia without TB disease, but not among patients with TB disease (aHR, 1.0; 95% CI, 0.8–1.2). Using 4 categories of RBG and restricted cubic spline regression, aHRs for death were significantly increased in patients with RBG of 110–140 mg/dL (categorical model: aHR, 1.3; 95% CI, 1.2–1.4; restricted spline: aHR, 1.1; 95% CI, 1.0–1.1) compared with those with RBG <110 mg/dL. Conclusions: Our findings highlight an urgent need to evaluate hyperglycemia screening and diagnostic algorithms and to ultimately establish glycemic targets for PLHIV with and without TB disease.